Simulating cosmic ray physics on a moving mesh - Pfrommer, Christoph; Pakmor, Rüdiger; Schaal, Kevin; Simpson, Christine M.; Springel, Volker (Monthly notices of the Royal Astronomical Society, 2017)
We discuss new methods to integrate the cosmic ray (CR) evolution equations coupled to magnetohydrodynamics on an unstructured moving mesh, as realized in the massively parallel arepo code for cosmological simulations. We account for diffusive shock acceleration of CRs at resolved shocks and at supernova remnants in the interstellar medium (ISM) and follow the advective CR transport within the magnetized plasma, as well as anisotropic diffusive transport of CRs along the local magnetic field. CR losses are included in terms of Coulomb and hadronic interactions with the thermal plasma. We demonstrate the accuracy of our formalism for CR acceleration at shocks through simulations of plane-parallel shock tubes that are compared to newly derived exact solutions of the Riemann shock-tube problem with CR acceleration. We find that the increased compressibility of the post-shock plasma due to the produced CRs decreases the shock speed. However, CR acceleration at spherically expanding blast waves does not significantly break the self-similarity of the Sedov-Taylor solution; the resulting modifications can be approximated by a suitably adjusted, but constant adiabatic index. In first applications of the new CR formalism to simulations of isolated galaxies and cosmic structure formation, we find that CRs add an important pressure component to the ISM that increases the vertical scaleheight of disc galaxies and thus reduces the star formation rate. Strong external structure formation shocks inject CRs into the gas, but the relative pressure of this component decreases towards halo centres as adiabatic compression favours the thermal over the CR pressure.
Published online: 17 November 2016
Gesehen am 25.10.2017